Does a human chorionic gonadotropin level of over 20, 000 IU/L four weeks after uterine evacuation for complete hydatidiform mole constitute an indication for chemotherapy for gestational trophoblastic neoplasia?. (April 2018) - Braga, Antonio; Biscaro, Andressa; do Amaral Giordani, Jessye Melgarejo; Viggiano, Maurício; Elias, Kevin M.; Berkowitz, Ross S.; Seckl, Michael J.
Abstract: Objective: To evaluate whether a human chorionic gonadotropin (hCG) level ≥20, 000 IU/L four weeks after uterine evacuation for complete hydatidiform mole (CHM) is an appropriate indicator for initiating chemotherapy for the treatment of gestational trophoblastic neoplasia (GTN). Study design: Historical database review of 1228 women with CHM who received treatment and follow-up between January 2000 and June 2013 at four Brazilian trophoblastic disease centers. The primary outcome measure was the progression from CHM to GTN. The secondary outcomes were the occurrence of uterine perforation, staging of GTN, WHO/FIGO risk score, and treatment (use of single- or multiagent chemotherapy). Results: An hCG level ≥20, 000 IU/L four weeks after uterine evacuation for CHM, while occurring in only 6.1% of women, was the most important risk factor for the development of postmolar GTN (adjusted RR = 5.83; p < 0.01; CI: 3.47–9.79), with a sensitivity of 36.8%, a specificity of 98.6%, a positive predictive value of 80%, and a negative predictive value of 91.1%. On the other hand, there were no differences in postmolar GTN stage, prognostic score, or need for multiagent chemotherapy relative to hCG level ≥20, 000 IU/L versus <20, 000 IU/L. Conclusions: Although hCG level ≥20, 000 IU/L four weeks after uterine evacuation for CHM was very predictive of development of post-molar GTN, delay in treatment until hCG plateau or increase did not affect outcomes, with no uterine perforations or treatment failures.